PENYAJIAN SOLIS MARIMBA REPERTOAR WINTER ANTONIO VIVALDI, NOCTURNE IN C SHARP MINOR FREDERIC CHOPIN - Toni Rahmat Putra; Ferry Herdianto; Hafif HR (Laga-Laga : Jurnal Seni Pertunjukan, 2021)
This article about percussion music performances in marimba playing techniques as an instrument presented by solis. presenting two repertoires namely Winter (L'Inverno) created by Antonio Vivaldi from the Baroque era in the 18th century, presented in the form of a marimba solis performance and a second repertoire of a by Frederic Chopin, Nocturne In C Sharp Minor in the Romantic era presented in Solis Marimba with accompaniment Ensamble of strings. The two repertoires presented have differences ranging from difficulty levels, styles, game techniquesABSTRAK Artikel ini memuat tentang pertunjukan musik perkusi dalam teknik bermain marimba sebagai instrument yang disajikan oleh solis. membawakan dua repertoar yaitu Winter (L’Inverno) diciptakan oleh Antonio Vivaldi dari era Barok pada abad 18, disajikan dalam bentuk pertunjukan solis marimba dan repertoar kedua sebuah karya Frederic Chopin, Nocturne In  C Sharp Minor pada era Romantic yang disajikan dalam Solis Marimba dengan iringan Ensamble string. Kedua repertoar yang disajikan  memiliki perbedaan mulai dari tingkat kesulitan, style, teknik permainan.